Silver Spoon and Green Lifestyle: A National Study of the Association between Childhood Subjective Socioeconomic Status and Adulthood Pro-Environmental Behavior in China - Liu Meiting; Koivula Aki (MDPI, 2022)
Based on the life history theory, this study is aimed at examining the associations among childhood subjective socioeconomic status, adulthood pro-environmental behavior, and commercial insurance purchase. We used the data from the 2013 Chinese General Social Survey (CGSS2013) and obtained a sample of 11,172 respondents, with ages ranging from 18 to 97 years old. The respondents were selected using multistage stratified sampling. Correlational, mediational and moderational analyses were conducted using SPSS. The results show that the childhood subjective socioeconomic status is positively associated with adulthood pro-environmental behavior, independent of the current subjective socioeconomic status. In addition, commercial insurance purchase acts as a mediator of the association between childhood subjective socioeconomic status and adulthood pro-environmental behavior. Using conditional process analysis, we demonstrated that age moderated both the path where childhood subjective socioeconomic status influenced adulthood pro-environmental behavior and the path where childhood subjective socioeconomic status influenced commercial insurance purchase. Theoretically, the results provide empirical support for evolutionary perspective on sustainable behavior and demonstrate that childhood environment can constrain individual consumer choices and lifestyle. Practically, positioning target customers to commercial insurance clients may be an effective marketing strategy to increase consumers' actual purchase of ethical products. Moreover, to realize environmental goals, social policy makers can make efforts to publicize the importance of insurance and expand the coverage of insurance by increasing the corresponding financial subsidies for low socioeconomic status families.